The Role of the Strategic Leader in Managing Change in the Algerian Institution - Mohammed Balkhir; Achouak Benkaddour (Social Empowerment Journal, 2021)
This article aims to identify the reality of strategic leadership in the Algerian institution, to know the extent to which the Algerian institution embodies the strategy of change, and to highlight the role and importance of strategic leadership in creating and leading change in the Algerian public institution.     The most important results of the study is that the public institution did not adopt any aspect related to the strategy despite its adoption of foresight. However, it remains a purely routine administrative work, in addition, to appointing managers and not leaders, and thus the absence of institutional diligence due to the absence of a change leader who carries the characteristics of a strategic thinker leader. In addition, the public educational and training institution no longer provides a basic training of human resources for institutions, but rather depends on an aspect that often determine by the original institution, or institutes and training schools, and is more technical related to work and production, which made institutions lack leadership legislation that carry out by higher authorities. The role of the director and the local leader is to implement the instructions and telegrams sent down.